Rising energy prices and the economics of water in agriculture - Zilberman, D.; Sproul, T.; Rajagopal, D.; Sexton, S.; Hellegers, Petra J.G.J. (IWA Publishing, 2008)
Rising energy prices will alter water allocation and distribution. Water extraction and conveyance will become more costly and demand for hydroelectric power will grow. The higher cost of energy will substantially increase the cost of groundwater, whereas increasing demand for hydroelectric power may reduce the price and increase supply of surface water. High energy prices and geopolitical considerations drive investment in land-and water-intensive biofuel technology, diverting land and water supplies to energy production at the expense of food production. Thus, rising energy prices will alter the allocation of water, increase the price of food and may have negative distributional effects. The impact of rising energy prices and the introduction of biofuels can be partly offset by the development and adoption of new technologies, including biotechnology. The models considered here can be used to determine the effects of rising energy prices on inputs, outputs, allocation decisions and impact on distribution.